The effect of ballot design for strawberry yogurt analysis using CATA (check-all-that-apply) - Jordán-Suárez, Oscar (2024)
Sensory evaluation of food is a constantly evolving field, where recently developed analysis methods are on their way to be consolidated. Check-All-That-Apply (CATA) is a rapid method used to describe sensory characteristics of a product through a personalized selection of terms; however, the format in which these terms are presented is not standardized. This study aimed to assess the effect of the design of four CATA ballots for the analysis of strawberry drinkable yogurt. Fifteen descriptive terms were established with the participation of 97 consumers, with 6 terms relating to texture, 5 to taste, and 2 to both appearance and odor. The four ballot models: a) columns, b) vertical list, c) radial distribution, and d) random distribution, were applied to characterize the same commercial brand of yogurt using 150 consumers for each model. According to Cochran’s Q test, significant differences were found for the pink color, acid/sour taste, strawberry odor, creaminess, viscosity, milk odor, and artificial flavor. Among the four ballot models, model C shows less variability in selecting terms. Furthermore, there were found differences among the yogurt samples for physicochemical properties (p-value<0.05) related to instrumental color, pH, titratable acidity, and soluble solids, except for consistency index. Finally, these findings highlight that the ballot design affects consumer responses associated with the visual perception process resulting from the design, as well as the physicochemical characteristics of yogurt derived from the technological process experienced during manufacturing and commercialization.